Deficiency of the paternally-expressed imprinted Peg3 gene in mice has sexually dimorphic consequences for offspring communication and social behaviour - Tyson, Hannah R.; Harrison, David J.; Higgs, Mathew J.; Isles, Anthony R.; John, Rosalind M. (Frontiers in Neuroscience, 2024)
Introduction Imprinted genes are expressed from one parental allele as a consequence of epigenetic processes initiated in the germline. Consequently, their ability to influence phenotype depends on their parent of-origin. Recent research suggests that the sex of the individual expressing the imprinted gene is also important. We have previously reported that genetically WT (WT) dams carrying and caring for pups mutant for Peg3 exhibit anxiety-like behaviours and their mutant pups show a reduction in ultrasonic vocalisation when separated from their mothers. Sex-specificity was not examined. Methods WT female mice were mated with WT, heterozygous Peg3-/+ or homozygous Peg3-/- studs to generate all WT (control), 50:50 mixed or 100% mutant litters, respectively, followed by behavioural assessment of both dams and their pups. Results We reproduced our original finding that WT dams carrying and caring for 100% mutant litters exhibit postpartum anxiety-like symptoms and delayed pup retrieval. Additionally, these WT dams were found to allocate less time to pup-directed care behaviours relative to controls. Male Peg3-deficient pups demonstrated significantly reduced vocalisation with a more subtle communication deficit in females. Postweaning, male mutants exhibited deficits across a number of key social behaviours as did WT males sharing their environment with mutants. Only modest variations in social behaviour were detected in experimental females. Discussion We have experimentally demonstrated that Peg3 deficiency confined to the offspring causes anxiety in mouse mothers and atypical behaviour including deficits in communication in their male offspring. A male-specific reduction in expression PEG3 in the fetally-derived placenta has previously been associated with maternal depression in human pregnancy. Maternal mood disorders such as depression and anxiety are associated with delays in language development and neuroatypical behaviour more common in sons. PEG3 deficiency could drive the association of maternal and offspring behavioural disorders reported in humans.